Level 26. 3., Temné odhalenia - Zuiker, Anthony E., 1968-; Swierczynski, Duane, 1972- (Ikar, 2012)
Elitný vyšetrovateľ Steve Dark opäť prekonáva zlo v sebe, aby mohol vypátrať toho najhoršieho z najhorších